Korelasi Sifat Fisik Biodiesel Campuran Jatropha - Kedelai: Densitas, Viskositas, Titik Nyala dan Nilai Kalor - Wahyudi Wahyudi (Yayasan Literasi Sains Indonesia, 2025)
The physical properties of biodiesel—such as density, viscosity, flash point, and calorific value—play a crucial role in determining its combustion performance, safety, and compatibility with diesel engines. This study aims to evaluate the correlation between these physical properties in biodiesel blends derived from various ratios of jatropha and soybean oil. Biodiesel was produced using standard esterification and transesterification processes. Each sample was then tested using ASTM-standard methods to determine density, viscosity, flash point, and higher heating value (HHV). The results revealed strong linear correlations among the measured parameters. Density exhibited a positive correlation with viscosity (R² = 0.8834) and flash point (R² = 0.9655), but a negative correlation with HHV (R² = 0.8312). Additionally, flash point was positively correlated with HHV (R² = 0.8416). These findings confirm that the blend ratio significantly influences biodiesel properties and that increasing soybean content improves heating value while reducing viscosity. The established correlations provide a scientific basis for formulating biodiesel blends that optimize combustion efficiency, enhance engine performance, and ensure safe handling and storage, thereby supporting more sustainable energy solutions.